Theoretical prediction by DFT on properties of β′-SrTa2O6 crystal - Aycibin Murat; Erzen Mehmet; Akkus Harun (Processing and Application of Ceramics, 2023)
Based on the Density Functional Theory (DFT) electronic band structure, state density, linear optics, elastic, dynamic and thermodynamic properties of β′-SrTa2O6 crystal with P4/mbm (No. 127) space group were investigated with the help of ABINIT and Wien2k code. In the study, it was found that the β′-SrTa2O6 crystal is classified as a semiconductor with an indirect bandgap. For this crystal, the dielectric function was obtained and optical constants such as energy loss function, extinction coefficient, absorption coefficient and reflectivity were calculated. The components of the elastic stiffness tensor, the phonon dispersion, the state density and the contribution of each atom to the state density were obtained. Finally, thermodynamic properties were determined for the β′-SrTa2O6 crystal. Furthermore, the changes in free energy (F), internal energy (E), entropy (S) and heat capacity (C) depending on the temperature were investigated.